Differences sella turcica morphology in Class II and III skeletal malocclusion patients aged 18-25 years in the Medical Radiology Laboratory, Faculty of Dentistry, Brawijaya University and Dental Clinic, Saiful Anwar Hospital: Perbedaan morfologi sella tursika pada pasien maloklusi skeletal Klas II dan III usia 18-25 tahun di Laboratorium Radiologi Fakultas Kedokteran Gigi Universitas Brawijaya dan Poli Gigi RS Saiful Anwar - Berliana Zulnadya Azmi; Nur Masita Silviana (Makassar Dental Journal, 2024)
Skeletal malocclusion is jaw disharmony due to abnormalities in jaw growth. Sella turcica is a main anatomy in radiographic analysis of neurocranial and craniofacial complex. Abnormalities of sella turcica have been associated with malocclusion. This study was to determine differences sella turcica morphology in Class II and III skeletal malocclusion patients aged 18-25 years. This analytical observational study with 15 subjects in each group of Class II and III skeletal malocclusion. The sample was determined into Class II and III skeletal by measuring the ANB angle and then determining the morphology of sella turcica by comparing it with the Axelsson classification. The results showed that there was no significant difference in sella turcica morphologyin Class II and III skeletal malocclusion patients aged 18-25 years (p>0.05). The conclusion is that the morphology of the sellaturcica in Class II and III skeletal malocclusion patients was not significantly different.